Analytical Solutions of Functionally Graded Curved Beams under an Arbitrarily Directed Single Force. (27th February 2019) - Zhang, Liangliang; Shang, Lange; Gao, Yang
Abstract : A functionally graded curved beam subjected to a shear tension force as well as a concentrated force at the free end is solved based on the inverse method, and a general two-dimensional solution is presented. The explicit expressions are derived by assuming that the elastic properties within curved beams vary in the radial direction according to a power law, i.e., E = E 0 r n, but are constant across the depth. After degenerating it into the isotropic homogeneous elastic cases, the results are in good consistency with existing analytical solutions. The stresses and displacements are firstly observed in different forms in terms of the different power function exponentn . These results will be useful as a guide for designing devices or as benchmark to assess other approximate methodologies.